PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN FISKUS, KESADARAN PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK BADAN - Refnini, Refnini; Indriani, Rini; Aprila, Nila (UNIB Press, 2016)
The purpose of the research was to prove the influence knowledge of tax, service quality of tax officers and awareness of taxpayers toward compliance of corporate taxpayer in Bengkulu City.The sample corporate taxpayer in Bengkulu City which taken by accidental sampling. The samplings are 83 respondents. The method of the data analysis used multiple regression analysis.The results from the data analysis showed that: understanding of tax, the service quality of tax officers and the awareness of taxpayers have positive and significant effect toward compliance of corporate taxpayers.